2018
DOI: 10.1002/ecy.2495
|View full text |Cite
|
Sign up to set email alerts
|

Mixed effects of an introduced ecosystem engineer on the foraging behavior and habitat selection of predators

Abstract: Invasive ecosystem engineers both positively and negatively affect their recipient ecosystems by generating novel habitats. Many studies have focused on alterations to ecosystem properties and to native species diversity and abundance caused by invasive engineers. However, relatively few studies have documented the extent to which behaviors of native species are affected. The red seaweed Gracilaria vermiculophylla (Rhodophyta) invaded estuaries of the southeastern United States within the last few decades and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 85 publications
1
21
1
1
Order By: Relevance
“…Studies of shorebird predator responses to A. vermiculophyllum are limited. In one recent study, Haram et al 2018 observed that shorebird density increased in response to A. vermiculophyllum in the southeastern U.S [7]. Likewise, shorebirds reached peak density on mats of Gracilaria spp.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies of shorebird predator responses to A. vermiculophyllum are limited. In one recent study, Haram et al 2018 observed that shorebird density increased in response to A. vermiculophyllum in the southeastern U.S [7]. Likewise, shorebirds reached peak density on mats of Gracilaria spp.…”
Section: Introductionmentioning
confidence: 96%
“…Exotic species that modify physical structure of environments exhibit bimodal impacts, depending on whether they increase or decrease habitat heterogeneity [1,3]. When exotic species add complexity or compensate for lost habitat complexity, the density and diversity of native biota increase [1,[3][4][5][6][7]. As heavily human-modified ecosystems become more common in the 21 st century, invasive species may provide conservation opportunities [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karena itu kelimpahan dan keanekaragaman jenis epibion yang hidup bersama kerang A trapezia dan C taxifolia lebih tinggi daripada yang hidup hanya bersama A trapezia. Meskipun introduksi perekayasa ekosistem dapat dilakukan untuk memperbaiki habitat, namun dalam hal ini perlu diketahui interaksinya dengan spesies asli yang telah ada karena bisa menimbulkan dampak negatif bagi habitat dan spesies asli (Haram et al, 2018).…”
Section: Fungsi Mengenali Prekayasa Ekosistemunclassified
“…The landscape structure is highly important because the provision of refuges affects the effectiveness of responses to predation risk (Heithaus et al, 2009). Predators prefer to forage where there is less cover for prey (Haram et al, 2018) whilst prey select locations with more refuges (Bishop & Byers, 2015). The availability of food in locations that are safe from predators have strong impacts on growth and reproduction in mice (Arthur et al, 2004) and fish (Crowder & Cooper, 1982), and refuge from predation also affect the timing of life history decisions such as maturation (Grof-Tisza et al, 2015).…”
Section: Introductionmentioning
confidence: 99%